Reformulation Of Islamic Educational Leadership In The Era Of Disruption - Azman, Zainal; Supriadi, Supriadi; Arikarani, Yesi (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2024)
This study discusses the urgent need for Islamic educational institutions to adapt to the rapid technological and societal changes that characterize the Era of Disruption. Traditional leadership practices in Islamic education must be re-evaluated to remain relevant and practical. This emphasizes the importance of integrating technology into educational practices while ensuring that these innovations are aligned with Islamic values. This article outlines several key strategies for reshaping Islamic educational leadership, including cultivating a disruptive mindset among leaders. A disruptive mindset, in this context, refers to a proactive and innovative approach to problem-solving, where leaders are encouraged to challenge the status quo and embrace change. This mindset is crucial in navigating the complexities of the digital era while upholding Islamic values. Other strategies include promoting self-driven initiatives and reshaping educational paradigms to meet contemporary needs. The research method used is a qualitative approach with a literature study. The results obtained are the importance of digital literacy and the ethical use of technology in preparing educators and students to face the challenges of the digital era. Developing professional training programs that equip educators with the skills necessary to utilize digital tools effectively while upholding Islamic principles is recommended. This article also emphasizes the importance of character education, encouraging institutions to foster moral and ethical values ??in addition to academic achievement, and, ultimately, the need for a comprehensive approach to leadership in Islamic education that balances technological advancement with preserving core Islamic teachings. By embracing innovation and cultivating a culture of continuous improvement, Islamic educational leaders can ensure that their institutions thrive in the Age of Disruption, producing knowledgeable and morally grounded individuals. This reformulation is essential to meet the needs of an evolving society and fulfill the mission of Islamic education in a rapidly changing world.